126k views
0 votes
Solve this equation. -4(p+2)+8=2(p-1)-7p+15

User Kewne
by
4.9k points

1 Answer

6 votes
Hey there!

First we have to
distribute!


-4 (p +2) = +8 = 2(p - 1) -7p + 15 \\ -4(p) + -4(2) + 8 = 2(p) +-2 + -7p + 15

Now, we have to
combine our like terms


-4p + (-8 + 8) = 2p + (-7p) + (-2) + 15

Once we solve all the
like-terms we get


-4p = 5p +13

Now, we have to
add
5p to each of your sides


-4p + 5p \\ = -5p + 13 + 5p

Solve that part of the equation


p= 13

Good luck on your assignment and enjoy your assignment

~
LoveYourselfFirst:)
User Stefan Dollase
by
5.0k points